2008
DOI: 10.5424/sjar/2008062-318
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of sunflower pollinators and their effect on seed yield in Makueni District, Eastern Kenya

Abstract: A field experiment was carried out in 2004 and 2005 to identify the diversity of sunflower (Helianthus annuus L.) pollinators and their influence on seed yield in Makueni district, a semi-arid area in Eastern Kenya. Insect flower visitors were recorded, pollen counted from their body and pollination efficiency index for each visitor determined. Seed yield from plots where insect visitors had access to and where they were denied access was compared. The proportional difference of yield from this pollination sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 12 publications
(9 reference statements)
9
29
1
4
Order By: Relevance
“…These results corroborate those found by Du Toit (1990), Nderitu et al (2008) and Oz et al (2009), who observed increasing on production of sunflower's seed in area with introduction of Africanized bees of 38 %, 53 % and 206 %, respectively, related areas without bees.…”
Section: Discussionsupporting
confidence: 82%
“…These results corroborate those found by Du Toit (1990), Nderitu et al (2008) and Oz et al (2009), who observed increasing on production of sunflower's seed in area with introduction of Africanized bees of 38 %, 53 % and 206 %, respectively, related areas without bees.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the high concentration of elaic acid in Oleko is rather anticipated (Skoric, 1992), however, the high concentration in 63A90 was probably due to cross pollination and the insects previously visited the high oleic hybrid (Table 4). Genotype is considered as the main factor that determines the oleic acid concentration as previously suggested by Fernandez et al (1989) and Izquierdo et al (2002), however, cross pollination by honeybees can affect the grain yield and oil content (Nderitu et al, 2008). Moreover, the high temperatures during grain filling until maturity may have also played an important role to the high values observed (Robertson et al, 1971;Anderson et al, 1978;Hazel et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Here we present a comparable analysis of the pollen of sunflower, Helianthus annuus (Asteraceae). This species, native to North America (Neff and Simpson, 1990), is a major annual oilseed crop worldwide, and pollination by honeybees improves seed production, seed mass and oil content (Krause and Wilson, 1981;Nderitu et al, 2008;Carvalheiro et al, 2011). In his study of honeybee behaviour on sunflowers, Free (1964) suggested that bees visit the florets mainly for nectar and discard excess pollen because it is less attractive than other pollens.…”
Section: Introductionmentioning
confidence: 99%